PENGARUH PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING DENGAN BANTUAN VIDIO PEMBELAJARAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS X IPA SMA N 3 PAYAKUMBUH - Febriani, Intan (Departemen Matematika, 2021)
Mathematics problem solving ability is one of the important abilities that students have in learning mathematics. However, students of class X MIPA SMA Negeri 3 Payakumbuh still lack this ability. The solution provided is to apply the Discovery Learning with the help of a learning video. This study aims to see the difference in mathematical problem solving skills of students who use Discovery Learning with conventional learning. The type of research used is quasi experiment with Randomized (DL) Control-Group Only Design. The population is X MIPA class students of SMA Negeri 3 Payakumbuh. Class XMIPA-3 and class XMIPA-5 as the sample class. Finally test in the form of an essay as an instrument. After the t-test was conducted, P-vaue=0.009 was obtained. Because the P-value <0.05 consequently reject . Therefore, it’s concluded that the level of mathematics problem solving ability of students using Discovery Learning assisted by learning videos is higher than using conventional.